INFEKSI MENULAR SEKSUAL PADA GAY DI TANGERANG, JOGJAKARTA DAN MAKASSAR TAHUN 2009 (ASPEK REKAM MEDIS PADA ANALISIS DATA STBP) - Nanda Aula Rumana (Indonesian of Health Information Management Journal (INOHIM), 2013)
AbstractThis journal discusses about factors that influence the incidence of STIs in MSM and implementation of quality improvement for health care quality through medical records of specific STI patients. It underlies the researchers conducted a study to determine the factors associated with the incidence of STIs in MSM in Jakarta, Jogjakarta and Makassar in 2009.This research is a descriptive study with cross sectional approach using secondary data Integrated Biological and Behavioral Surveillance (STBP) 2009. The samples of this study are men who have sex with men (MSM) with 599 respondents in Jakarta, Yogyakarta and Makassar. MSM outreach methods using methods respondents Driven Sampling (RDS). This study shows that the proportion of MSM infected with STDs by 32%. The factors that proved significant to the incidence of STIs in MSM is the age (Pvalue = 0.02), age of first risk behavior (Pvalue = 0.004), main source of income (Pvalue = 0.000), and condom use (Pvalue = 0.037) , the type of lubricant (Pvalue = 0.003), and the number of sexual partners (Pvalue = 0.003). Aspects of medical records necessary to review medical records at the hospital so that a history of STI patients can be better traced so that the transmission to others can be overcome and prevent possible toward the gate of HIV / AIDS. Based on this research to be the addition of a variable type of lubricant because it proved significantly associated with incidence of STIs in MSM, but not in the form of medical recordsKeywords: sexually transmitted diseases, man who sex with man, hiv/aids